KURANGNYA TINGKAT PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI - Ni Putu Aryani; Susilia Idyawati; Anna Layla Salfarina (Stikes Yarsi Mataram, 2022)
Adolescence is the period when the development of the reproductive organs begins. Adolescence is a period that is considered vulnerable in life because it is a period of transition from a child's life to a turbulent adult life. Providing information on sexual problems is even more important considering that adolescents are in an active sexual potential. Lack of knowledge of adolescents about reproductive health can cause problems in their reproductive health. Problems that will arise if adolescents do not know sufficient knowledge about reproductive health, namely sexually transmitted diseases and sexually transmitted infections. The purpose of this study was to determine the level of knowledge of adolescents about reproductive health. The method used in this implementation is a lecture conducted through counseling. This activity is a means to educate teenagers.